Cartographies of Exploitation: Multi-Scalar Governance and Structural Violence in Nigeria’s Child Trafficking Networks - Omoigberale, Omonye; Anyanwu, Emmanuella (Journal of Contemporary International Relations and Diplomacy, 2025)
This study interrogates the structural and geopolitical determinants of child trafficking in Nigeria, situating the phenomenon within globalized circuits of informal labour and the logics of structural violence. Employing a mixed-methods design—comprising geospatial analysis, 600 household surveys, and 32 semi-structured interviews across Benue, Edo, Borno, and Lagos States—the research uncovers trafficking’s spatial concentration in infrastructurally neglected rural hinterlands, peri-urban margins, and high-mobility transit corridors. Poverty is identified as the primary structural driver, exacerbated by chronic unemployment, educational disenfranchisement, and multi-dimensional precarity. The study foregrounds the role of contested multi-scalar governance: while institutions such as NAPTIP operate within formal legal frameworks, traditional authorities often exercise competing normative power, reproducing culturally sanctioned forms of complicity. Typologies of trafficking uncovered reflect Nigeria’s insertion into transnational labour markets, with victim trajectories frequently culminating in the Gulf States and Europe—underscoring the embeddedness of global capital in exploitative shadow economies. Rather than framing trafficking as discrete criminal deviance, the study theories it as an epiphenomenon of deeper structural pathologies: spatial injustice (the peripheralisation of rural zones), normative complicity (entrenched patriarchal clientelism), and systemic developmental exclusion. The study calls for spatially differentiated and survivor-centered policy interventions that integrate anti-poverty frameworks, devolved governance mechanisms, and locally anchored accountability systems. Ultimately, it argues for a reconstitution of Nigeria’s global political-economic entanglements—via SDG-aligned cooperation and robust enforcement of the Palermo Protocol’s transnational justice provisions—as preconditions for dismantling the generative mechanisms of child trafficking.